2002
DOI: 10.1161/01.hyp.0000025146.19104.fe
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Eplerenone Added to Renin-Angiotensin Blockade in Hypertensive Patients

Abstract: Abstract-The efficacy and tolerability of eplerenone, a selective aldosterone blocker, was assessed when added to existing antihypertensive therapy with an ACE inhibitor or an angiotensin II receptor blocker (ARB). Hypertensive patients (nϭ341) whose blood pressure (BP) was not controlled despite ACE inhibitor or ARB were randomized (double-blind) to receive 50 mg eplerenone (increasing to 100 mg if required) once daily or placebo for 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(110 citation statements)
references
References 20 publications
6
101
0
3
Order By: Relevance
“…Clinical research to date has shown that eplerenone when used alone or with other major antihypertensive drugs achieves excellent antihypertensive effects. [13][14][15][16][17][18][19][20] One of the intriguing properties of eplerenone is that its antihypertensive effect is not compromised in low-renin hypertensive patients, which means that it reduces blood pressure independently of the patient's renin profile. [14][15][16]26 This property makes eplerenone effective for Japanese patients who tend to have high salt intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical research to date has shown that eplerenone when used alone or with other major antihypertensive drugs achieves excellent antihypertensive effects. [13][14][15][16][17][18][19][20] One of the intriguing properties of eplerenone is that its antihypertensive effect is not compromised in low-renin hypertensive patients, which means that it reduces blood pressure independently of the patient's renin profile. [14][15][16]26 This property makes eplerenone effective for Japanese patients who tend to have high salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…19 Therefore, among the adverse events involving hyperkalemia due to eplerenone, renal impairment is the one requiring the most attention. This point should always be kept in mind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose-related increases in active plasma renin and aldosterone are seen 12 to 24 hours after eplerenone administration. 61,64 The change in PRA and aldosterone during 400 mg/d dosing was equivalent to that observed during spironolactone 50 mg BID; the aldosterone response to 200 mg BID eplerenone was significantly greater. Addition of 50 to 100 mg/d eplerenone to treatment with ACE inhibitor or AT 1 receptor antagonist increased active plasma renin 92.5% and 95.9%, respectively, and serum aldosterone 70.3% and 60.4%, respectively.…”
mentioning
confidence: 86%
“…Krum et al 64 reported the hypotensive effect of add-on therapy with eplerenone (50 mg increasing to 100 mg) in patients who were already taking an ACE inhibitor (nϭ177) or an AT 1 receptor antagonist (nϭ164). Coadministration of eplerenone significantly reduced seated systolic blood pressure compared with coadministration of placebo in both the ACE-inhibitor and AT 1 receptor antagonist groups.…”
Section: Efficacy Hypertensionmentioning
confidence: 99%